APLIKASI PUPUK KALIUM CAIR PLUS UNTUK MENINGKATKAN KUALITAS BAWANG MERAH DI ADIPALA, CILACAP - Syarifah, Kharirotus; Faozi, Khavid; Rostaman, Rostaman; Saparso, Saparso (Agrin, 2023)
One of the important factors influencing crop production is nutrition, which depends on soil fertility and fertilizer application. Nutrition will affect the weight loss of shallots. Shallots can loss weight loss of 25-40% during drying and 17% during storage. One of the nutrients that affect weight loss is potassium. Potassium is an element that plays an important role for plants in the process of photosynthesis, energy storage, protein synthesis, translocation of photosynthetic products. Potassium also plays a role in protecting the osmotic potential of plants in regulating the closing and opening of stomata so that plants can maintain water conditions which will have a good impact on photosynthesis and the flow of assimilate from leaves to plant parts. This study aimed to determine the effect of liquid potassium fertilizer plus application on the quality of shallots. The research was conducted in Adipala, Cilacap which has a height of 10 m above sea level and a temperature ranging from 23-30o C. The land area used is 50 m2. The study was conducted from June 2021 to September 2021. This study used a non-factorial randomized block design with four treatments, namely (1) 0 ml/plot, (2) 1 ml/plot, (3) 1.5 ml/plot, and (4) 2 ml/plot with ten replications. Data were analised using Anova and than follow DMRT at error 0,5%. The variables observed were: plant height, number of leaves, number of bulb, total fresh weight, total dry weight of askip, bulb diameter, bulb hardness and crop yield/plot. The results showed that the application of liquid potassium fertilizer plus had no significant effect on plant height, number of leaves, number of bulb, total fresh weight, total dry weight of askip, blub diameter, and crop yield/plot, but significantly affected the hardness of shallot bulbs.